2014
DOI: 10.1002/ijop.12054
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between stressful life events during childhood and differentiation of self and intergenerational triangulation in adulthood

Abstract: This study examined the relationships between stressful life events in childhood and differentiation of self and intergenerational triangulation in adulthood. The sample included 217 students (173 females and 44 males) from a college in northern Israel. Participants completed the Hebrew versions of Life Events Checklist (LEC), Differentiation of Self Inventory-Revised (DSI-R) and intergenerational triangulation (INTRI). The main findings were that levels of stressful life events during childhood and adolescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
1
13
0
2
Order By: Relevance
“…It is an all-too-common, but dysfunctional, way for two persons in the family, typically mother and father, to manage their conflicts and tensions by bringing or entangling a third party, often a child, in the process. Most relevant work to date on triangulation indicates that such child involvement in parental conflicts adversely affects child and adolescent well-being (e.g., Bell, Bell, & Nakata, 2001; Bosco, Renk, Dinger, Epstein, & Phares, 2003; Buehler, Franck, & Cook, 2009; Buehler & Welsh, 2009; Etkin, Koss, Cummings, & Davies, 2014; Frank & Buehler, 2007; Fosco & Grych, 2010; Peleg, 2014; Peris, Geoke-Morey, Cummings, & Emery, 2008; Wang & Crane, 2001; Wang & Wang, 2014). Most of this research, however, has been carried out in the West.…”
mentioning
confidence: 99%
“…It is an all-too-common, but dysfunctional, way for two persons in the family, typically mother and father, to manage their conflicts and tensions by bringing or entangling a third party, often a child, in the process. Most relevant work to date on triangulation indicates that such child involvement in parental conflicts adversely affects child and adolescent well-being (e.g., Bell, Bell, & Nakata, 2001; Bosco, Renk, Dinger, Epstein, & Phares, 2003; Buehler, Franck, & Cook, 2009; Buehler & Welsh, 2009; Etkin, Koss, Cummings, & Davies, 2014; Frank & Buehler, 2007; Fosco & Grych, 2010; Peleg, 2014; Peris, Geoke-Morey, Cummings, & Emery, 2008; Wang & Crane, 2001; Wang & Wang, 2014). Most of this research, however, has been carried out in the West.…”
mentioning
confidence: 99%
“…Several longitudinal studies [51,52] confirm the data produced by crosssectional studies providing empirical evidence about the significant correlations between family relationships during adolescence and functioning in adulthood. More specifically to the BFST, Peleg [6] demonstrated that individuals who have experienced more stressful life events in childhood and adolescence are of lower DoS and more prone to be involved in intergenerational triangulation, which, in turn, leads to inadequate coping with future stressful events. Such results alongside the results obtained in Study 3 tend to the conclusion that good interparental relationship quality creates a positive emotional environment for children and serves as a protective factor for children's well-being in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that more favorable interactions with a spouse/partner usually predict better health as well as psychological well-being outcomes of an adult [1][2][3]. Additionally, the newest data suggest that broader family interactional context accounts for the significant changes in a person's physical health and morbidity as well as in psychosocial functioning (e.g., [4][5][6][7][8][9]). Thus, the body of research provides clear evidence that supports the necessity to understand physical health and psychological well-being from a systemic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Peleg (2014) also examined the relationship between stressful life events in childhood, differentiation of self during adulthood, and intergenerational triangulation. Peleg's (2014) research revealed that the level of stressful events that occurred during childhood and adolescence, in both genders, is positively correlated with the level of dependency on others and intergenerational triangulation, which are two subscales of differentiation of self. Furthermore, the level of positive life events experienced by an individual during childhood was shown to be negatively correlated with the level of emotional reactivity and emotional cutoff, another two subscales of DSI-R.…”
Section: Discussionmentioning
confidence: 99%